The Arctic expedition of 1875-6 : compiled from official sources with a summary of previous adventures in the Arctic seas - Johnston, R. (Robert).; Tower, Joseph Tuckerman, 1897-1931, former owner. hou (London : F. Warne & Co., 1877)
"Maps and illustrations." Mode of access: Internet.